PERANAN BIROKRASI PEMERINTAHAN DALAM PEMBERIAN PELAYANAN PERIZINAN ( KASUS DI KOTA BANJARMASIN ) - Samahuddin Muharram (Indonesian Journal of Dialectics, 2011)
The phenomenon that made the object of this research is the role of government bureaucracy in providing licensing services to the community in the city of Banjarmasin in which the agency used as a locus of research is in the Integrated  Licensing Agency and Investment Banjarmasin. The purpose of this study was to obtain a new concept regarding the role of government bureaucracy in providing licensing services as a contribution to advancing the science of government.      This research uses qualitative research approach with a purposive sampling technique. Secondary data collection using literature studies, studies of documents and observations. Primary data collection using interviewing techniques. Processing of data using descriptive analysis method.      The conclusion of the discussion of research results are as follows: The role of government bureaucracy  in granting permits in the city of Banjarmasin servant namely: the regulator under the legislation, the initiator of the policy, internal bureaucratic desire for power, security and compliance.      In this study discovered a new concept, that the role of government bureaucracy in licensing service delivery does not match the expectations of the public because of government bureaucracy has not been characterized by the organizational structure-adaptive, resulting in e more important service personal and group interest rather than society, and accurs dualism of service in the bureaucracy. Then the government bureaucracy in providing licensing services to communities affected by environmental factors, both internal and external.